Transformasi Pemerintahan Kolaboratif dalam Pengendalian Pencemaran Limbah Sludge Oil untuk Pencapaian Blue Economy di Bintan - Ryan Anggria Pratama; Dhani Akbar (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2020)
The strategic role of the Riau Islands as world trade traffic and a center of activity in the Riau Islands Province can be reached from Singapore with a distance of approximately 1 - 2 hours by sea transportation which has a bad impact, one of which is the pollution of sludge oil waste that often occurs in waters. Bintan since the 1960s and threatening Bintan waters. This study used a qualitative research method with a case study of Sludge oil in Bintan. The data was collected by means of document analysis, site analysis and other methods that produce descriptive data. The Operational Unit for the response to the oil spill must consist of representatives from the Ministry of Transportation, Ministry of Environment, BASARNAS, Ministry of Energy and Mineral Resources, Ministry of Home Affairs, Ministry of Foreign Affairs, Ministry of Marine Affairs and Fisheries, Ministry of Health, Ministry of Forestry, Ministry of Finance, Ministry of Law and Human Rights, TNI- AL, POLRI, BPMIGAS, BPHMIGAS, Governors, Regents / Mayors, part of which includes the sea and Oil and Gas Companies. The efforts made by the government have not been optimal enough and there is a need to move from the old way to the new way, including every actor, be it Government Actors or non-government actors. This makes it easier for the government to formulate and even implement countermeasures that ensure that the same violations do not happen again. Given that these violations can harm the state, society, and even nature.